Genetic susceptibility to the development of primary open angle glaucoma (Ukrainian Journal of Ophthalmology, 2026)
Background: Primary open angle glaucoma is a multifactorial optic neuropathy and associated with a number of factors such as age, ethnicity, family history, central corneal thickness, and intraocular pressure (IOP). In addition, it might be associated with myopia and certain systemic disorders. Family history is the highest risk factor as shown by the presence of glaucoma in first-degree relatives.Purpose: To assess the potential for the development of glaucoma due to genetically predisposed features of ocular anatomy and age-related changes in these features based on a case glaucoma in monozygotic siblings.Materials and Methods: We analyzed the clinical case of two monozygotic sisters with the disease based on complaints, history, physical and instrumental examination, treatment and outcomes.Results: The two monozygotic sisters (1) were diagnosed with the same disorder approximately at the same age, (2) presented with similar ocular biometric characteristics and age-related changes of the anterior eye,  and (3) underwent the same surgery on both eyes, which resulted in improved visual functions, stable IOP reduction, stable perimetric visual fields, and stable OCT derived RNFL thickness.Conclusion: The results obtained in monozygotic siblings confirm that genetic susceptibility to changes in anterior eye parameters and age-related changes in anterior ocular structures along with environmental factors constitute the main cause of hydrodynamic impairment resulting in the development of glaucoma.
Keywords: open angle glaucoma; anterior chamber depth; lens thickness; corneal thickness; pseudoexfoliation syndrome